“Elaboración de una guía de aplicación de métricas de calidad para metodologías ágiles de desarrollo web en www.machalamovil.com” - Muñoz Córdova, Edison Bolívar (2017)
The information and communication application development industry is facing significant advances today and will continue to do so in the future, the development of quality software is one of these advances in conjunction with support in standards and standards to build technologies effectively. The massive growth of the WWW, as an effect of the development of web technologies linked to the evolution of the users experience, has established the concept of Web systems without restriction of place, time and access, since it intends that the designs are More flexible, configurable and can respond to the dynamism of the context. In this context of greater competitiveness and with users who demand quality and innovation is not enough to provide functionality, we must develop stages of the software production process to manage their quality. The quality management is gradually gaining importance, and the role of the user is emphasized that through its appreciation and opinions, it gives us information to direct towards a better product. One of the weaknesses that web developers face is that they do not have a help guide to correctly apply a series of processes or measures that strengthen the quality control and evaluation when building a web application . This research aims to create a guide to quality metrics for the best development of web technologies supported by agile methodologies, and to have a document that reveals the requirements to evaluate the software and thus help the development or audit of any computer application Of this field, taking into account that at present it is very important for public or private companies to invest in this type of communication technologies, which prove the quality at the moment of its putting into production, where failures are manifested, Translating this into losses. In addition, with the preparation of this guide, it is expected to provide assistance in the development of quality applications, based on standards and standards that will allow a reliable product to be attained, as the need to achieve satisfaction is now very high. Customer, the added value that quality involves exploring more demanding markets. Based on this, the international norms or standards of information technologies such as ISO / IEC will be analyzed, in which several parameters of quality evaluation will be applied, such as the internal, external quality and in use of the software product, for the purpose of this Analysis was used a variety of tools to analyze the evaluation parameters mentioned above valuing most of their criteria. The results obtained through the use of the guide in conjunction with the appropriate standards and the support of the tools for evaluating the quality parameters, showed the strengths and shortcomings of the website that has been studied, leaving Thus uncovering the criteria to be improved.